Evidence for Residual Melt Extraction in the Takidani Pluton, Central Japan. (19th July 2017) - Hartung, Eva; Caricchi, Luca; Floess, David; Wallis, Simon; Harayama, Satoru; Kouzmanov, Kalin; Chiaradia, Massimo
Abstract: The Takidani pluton represents one of a few locations where melt extraction from a crystal mush is preserved in the natural rock record, making it an extremely good case study for investigating the generation of evolved melt reservoirs in the upper crust. Located in the Japan Alps, the Takidani pluton shows a clear vertical zonation consisting of granite and granodiorite in the lower and middle section, a fine-grained porphyritic granitic unit in the upper section and a marginal granodiorite at the roof contact with the host-rock. We present a detailed petrographic and geochemical study using samples collected along a section that traverses the entire vertical section of the pluton. No sharp contacts are found between units. Instead, gradual changes in rock fabric and mineralogy are observed between the lower granodiorite and overlying porphyritic unit. Major and trace element bulk-rock compositions show sigmoidal variations from the bottom to top of the pluton. Incompatible elements and silica contents increase roofwards within the porphyritic unit. Plagioclase chemistry reveals three main crystal populations (P1, P2 and P3) with Fe contents increasing towards the base of the pluton. Comparison with existing crystallization experiments, thermobarometry and hygrometry indicate that the magmas were emplaced at around 200 MPa, 850–900°C and bulk water contents of 3–4 wt %. Whole-rock major and trace element analyses together with mineral chemistry and textural observations suggest that the fine-grained porphyritic unit was extracted from the underlying granodiorite at temperatures between 800 and 740°C and crystallinities of 45–65 wt %. Radiogenic isotopes indicate only minor assimilation (2–6 wt %) and support melt evolution through crystal fractionation. The fine-grained matrix of the porphyritic unit may have been the result of pressure quenching associated with a volcanic eruption.